''Why should we teach children who can't learn? - Kupfer, Maria Cristina M.; Petri, Renata (Clinical Styles. The Journal on the vicissitudes of childhood, 2000)
In this paper, we discuss that the individual differences, which are on the basis of special education, are not natural, but historically determined. The creation of school in modern world produces, at the same time, the special child. Thus, the school faces great difficulties in reabsorbing that child. We also discuss the inclusion of psychotic and autistic children, and we believe that this inclusion is therapeutic for them. Finally, we discuss the idea that the inclusion should be done in all cases.